2022
DOI: 10.1177/08853282211066246
|View full text |Cite
|
Sign up to set email alerts
|

Poly(L-co-D,L lactic acid-co-Trimethylene Carbonate) 3D printed scaffold cultivated with mesenchymal stem cells directed to bone reconstruction: In vitro and in vivo studies

Abstract: A recent and quite promising technique for bone tissue engineering is the 3D printing, peculiarly regarding the production of high-quality scaffolds. The 3D printed scaffold strictly provides suitable characteristics for living cells, in order to induce treatment, reconstruction and substitution of injured tissue. The purpose of this work was to evaluate the behavior of the 3D scaffold based on Poly(L-co-D,L lactic acid-co-Trimethylene Carbonate) (PLDLA-TMC), which was designed in Solidworks™ software, project… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 62 publications
1
3
0
Order By: Relevance
“…Although the calcification zone in the tidemark was not as clear as the original cartilage the transition of subchondral bone is welldefined but contains high lacunar spaces. These results demonstrated that the presence of the PLDLA-TMC scaffold aided in the meniscal regeneration process, as shown by Esposito et al 35 It is evident that the results obtained with the implantation of a polymeric scaffold, without cell precultivation, provide better outcomes when compared to the empty defect group, 13 which represents an advancement and an alternative for the treatment of meniscus injuries in orthopedic practice.…”
Section: In Vivo Microscopy Evaluationsupporting
confidence: 53%
See 3 more Smart Citations
“…Although the calcification zone in the tidemark was not as clear as the original cartilage the transition of subchondral bone is welldefined but contains high lacunar spaces. These results demonstrated that the presence of the PLDLA-TMC scaffold aided in the meniscal regeneration process, as shown by Esposito et al 35 It is evident that the results obtained with the implantation of a polymeric scaffold, without cell precultivation, provide better outcomes when compared to the empty defect group, 13 which represents an advancement and an alternative for the treatment of meniscus injuries in orthopedic practice.…”
Section: In Vivo Microscopy Evaluationsupporting
confidence: 53%
“…8 The processing conditions applied indicated that the PLDLA-TMC polymeric scaffold presented a molecular weight of 192.764 g.mol À1 , which is a desired molecular weight requirement to the mechanical properties for a wide range of applications in bone/cartilaginous tissue engineering approaches, as previously reported. 13…”
Section: Gel Permeation Chromatography (Gpc)mentioning
confidence: 99%
See 2 more Smart Citations